Differences in Internal and External Load Between Adult and Youth Soccer Players in a Friendly Match - Aedo-Munoz, E (Archivos de Medicina del Deporte, 2022)
Objective: To determine differences in internal and external load during an unofficial match between First Division Adult and U-19 players of the same club using portable global positioning systems. Methods: During an unofficial match between an adult and a U-19 category, internal load through heart rate and external load through running performance were monitored. Seven adult players (25.57 ± 5.06 years) and five U-19 players (18.6 ± 0.54 years) were monitored. Comparisons were made between categories in the first half, second half and total match using the Mann-Whitney U test and calculating effect sizes through percent difference (PD). Results: Differences were found (p<0.05) of external load in maximum speed in first half and total match, with U-19 players reaching the highest values (maximum speed first half: 32.34 vs 27.77 km/h and PD = 15.3%; total match: 32.6 vs 28.14 km/h and PD = 14.7%). On the other hand, differences in internal load were only found in heart rate zone 3 (70 to 80% of maximum HR) in the first and second half, where U-19 players spent more time in this zone (heart rate zone 3 first half: 6.1 vs 1.73 minutes and PD = 111.6%; second half: 20.49 vs 5.21 minutes and PD = 118.8%). No differences were found in the other variables analyzed. Conclusion: From the results obtained we can conclude that there are no differences in internal and external load in adult players with U-19 players, except for maximum speed and heart rate zone 3 in this team during a non-official match. Therefore, for practical purposes, the U-19 players of this team could be in conditions to face the physical demands required by the adult category competition. © 2022 Archivos de Medicina del Deporte. All rights reserved.